Modelling agroecological transitions in Soudano-Sahelian agro-sylvo-pastoral territories: Promoting agro-landscape transformation - Delay, Etienne; Césaro, Jean-Daniel; Alassan, Bah; Masse D.; Fallot, Abigail; Perrotton, Arthur; Chapron, P.; Leclaire, M.; Reuillon, R.; Broutin, L.; Fievet, E. (2024)
This report focuses on modeling studies of agroecological transitions in the Soudano-Sahelian region, specifically at the Niakhar Observatory in the Fatick Region, where agriculture, forestry, and pastoral activities are integrated. The objective is to support and encourage the transformation of these landscapes towards greater sustainability and resilience. This involves co-constructing pathways of change with local communities and supporting them in collective actions aimed at restoring land, increasing crop yields, and fostering stronger community engagement.